2019
DOI: 10.1002/wer.1275
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in the sediment of Lake Ulansuhai of Yellow River Basin, China

Abstract: As an emerging organic pollutant, microplastics in the ocean have been the subject of much study. However, there is a lack of research on freshwater environments, notably in sediment, China. Microplastics contamination in sediment of Lake Ulansuhai has been investigated in the study, and its concentration range was from 24 ± 7 to 14 ± 3 n/kg. Further, it exhibited a difference in spatial distribution with high content in the north zone of the lake far from the entrance of the drainage canal and it has a decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 62 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…2 ). Previous freshwater studies like Dongting Lake (Jiang et al, 2018 ), Taihu Lake (Su et al, 2016 ), Poyang Lake (Yuan et al, 2019 ), Red Hills Lake (Gopinath et al, 2020 ), Lake Ulanshuhai (Qin et al, 2020 ), and Lake Mead National Recreation Area (Baldwin et al, 2020 ) also reported fibers as the dominant type of microplastic. The greater abundance of fibers in Phewa Lake sediments can be linked to domestic waste input, cage fish culture and fishing, washing clothes at the bank of the lake, the use of ropes in boasts, and cigarette butts lying on the shore.…”
Section: Resultsmentioning
confidence: 94%
“…2 ). Previous freshwater studies like Dongting Lake (Jiang et al, 2018 ), Taihu Lake (Su et al, 2016 ), Poyang Lake (Yuan et al, 2019 ), Red Hills Lake (Gopinath et al, 2020 ), Lake Ulanshuhai (Qin et al, 2020 ), and Lake Mead National Recreation Area (Baldwin et al, 2020 ) also reported fibers as the dominant type of microplastic. The greater abundance of fibers in Phewa Lake sediments can be linked to domestic waste input, cage fish culture and fishing, washing clothes at the bank of the lake, the use of ropes in boasts, and cigarette butts lying on the shore.…”
Section: Resultsmentioning
confidence: 94%
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/nano12132256/s1, Figure S1: The process of forming large plastics into microplastics, Figure S2: Schematic representation of the six sorption mechanisms, Table S1: Classification of microplastics, Table S2: Surface area parameters of different adsorbents, Table S3: Adsorption mechanism of organic pollutants, Table S4: Adsorption mechanism of inorganic pollutants, and Table S5: Adsorption mechanism of other pollutants [128][129][130][131][132][133][134].…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…From the perspective of the in uence depth of environmental factors, the thickness should be within 10 cm of the top silt (Liu et al, 2017). In addition, sediment core within 10 cm in shallow lakes is easily to be re-suspended by waves into the water (Qin et al, 2020). Furthermore, the species and biomass of microorganisms and benthic animals are abundant in the top 10 cm layer sediments, resulting in signi cant benthic disturbances, especially around the depth of 5.75±5.67cm in global waters (Lgab et al, 2015).In this study, we sampled undisturbed sediment columns of 20 cm from the top sediment, which should be deep enough to simulate the external interference.…”
Section: Reliability Of the Laboratory Simulations And Extrapolationmentioning
confidence: 99%